ANALISIS PERMINTAAN TAKSI KONVENSIONAL DI TENGAH BEROPERASINYA TAKSI ONLINE DI KOTA MAKASSAR (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2018)
The following is the new author guidelines and article templates of Equilibrium journal published by Faculty of Economics Wijaya Kusuma Surabaya University. The Article should be started with the Title of Article followed by Author/s’ Name/s and Affiliation and email  address. This abstract must be typed in Times New Roman font, Italic, 11 pt with total number of words 200-250, using 25 mm left margin, 30 mm top margin, and 20 mm right and bottom margins. The abstract should only be typed in one paragraph and one-column format. The single spacing should be used between lines in this abstract and body text. If the article is written in Indonesian, the abstract must be in English using the same style as English article. The abstract should be typed as concise as possible and should be composed of: problem statement, research methodology, scientific findings, and brief conclusion.